The committee appointed at the last January session of the General Assembly "to examine into the condition of the Narragansett tribe of Indians, to ascertain the number of the tribe and of their poor, and the expense or probable expense of supporting the poor, the annual income of the tribe, the amount of their debts, the quantity and volume of their land and all such other matters as they might deem important for enabling the House of Representatives to have a correct view of the affairs and necessaties of said Indian tribe . - King, Dan, 1791-1864
November 1, 1832 Report of Dan King and Benjamin B. Thurston regarding the conditions of the Narragansett Indians for the General Assembly. Included was an assessment of the finances, number of poor and ability to care for them, amount of debts and other relevant matters. The committee suggested that a guardian be appointed to take over the tribal land for their benefit, given the destitute and "forlorn" nature of the tribe. The committee also accused certain individuals of embezzling all the public funds. A bill was proposed, although not part of this document.